Analisis Sistem Informasi Driver Maxim Indonesia Menggunakan Pendekatan Evaluasi Usability Heuristik dan Human Resource Information System - M Rizeki Yuda Saputra; Agus Firdaus; Syahrial Shaddiq (P3M Politeknik Negeri Banjarmasin, 2023)
Driver information system analysis includes evaluation and in-depth understanding of various aspects of the system used by drivers in a service or platform. Driver information system analysis helps ensure that the technology infrastructure that supports driver operations in application-based transportation services is efficient, safe, and in line with business and driver needs. This research aims to analyze the usability of the driver information system with a case study of the Maxim driver information system. The method used to analyze Maxim drivers uses the Heuristic Evaluation (HE) and Human Resource Information System (HRIS) approaches. The research results found that the Maxim driver information system is easy to use and the information contained in it is quite clear.